Evaluation of The Genotoxicity of Three Food Additives using CHO-K1 Cells under in vitro Micronucleus Flow Cytometry Assay - Beni Lestari; Dhania Novitasari; Herwandhani Putri; Sari Haryanti; Ediati Sasmito; Edy Meiyanto (Indonesian Journal of Cancer Chemoprevention, 2017)
Exposure of genotoxic substances come from various sources such as food additives. The aim of this study is to evaluate the genotoxicity of food additives in CHO-K1 cells by micronucleus test flow cytometry. The food additives: sodium saccharine (SS), monosodium glutamate (MSG), and sodium benzoate (SB) were assessed by in vitro cytotoxicity and genotoxicity using Chinese Hamster Ovary-K1 (CHO-K1) cells. The cytotoxic effect of those compounds was evaluated by MTT Assay on CHO-K1 Cells. The genotoxic evaluation was observed by in vitro micronucleus test by flowcytometry with double staining method. The results showed that the three compounds did not perform cytotoxic effect, increased the frequency of micronucleus, and changed the cell cycle profiles. In general, these studies obtained that none of three food additives showed cytotoxic and genotoxic effect on CHO-K1 cells. Micronucleus test using flow cytometry is suitable for this purpose study.Key words : food additives, genotoxic, cytotoxic, micronucleus